Discovery of Orally Available Prodrugs of Itaconate and Derivatives - Lee, Chae Bin; Šnajdr, Ivan; Tenora, Lukáš; Alt, Jesse; Gori, Sadakatali; Krečmerová, Marcela; Maragakis, R Michael; Paule, James; Tiwari, Sandhya; Iyer, Jitesh; Talwar, Rashmi; Garza, Luis; et al. (Journal of medicinal chemistry, 2025)
Itaconate, an endogenous immunomodulator from the tricarboxylic acid (TCA) cycle, shows therapeutic effects in various disease models, but is highly polar with poor cellular permeability. We previously reported a novel, topical itaconate derivative, SCD-153, for the treatment of alopecia areata. Here, we present the discovery of orally available itaconate derivatives for systemic and skin disorders. Four sets of prodrugs were synthesized using pivaloyloxymethyl (POM), isopropyloxycarbonyloxymethyl (POC), (5-methyl-2-oxo-1,3-dioxol-4-yl) methyl (ODOL), and 3-(hexadecyloxy)propyl (HDP) pro-moieties pairing with itaconic acid (IA), 1-methyl itaconate (1-MI), and 4-methyl itaconate (4-MI). Among these, POC-based prodrugs (P2, P9, P13) showed favorable stability, permeability, and pharmacokinetics. Notably, P2 and P13 significantly inhibited Poly(I:C)/IFNγ-induced inflammatory cytokines in human epidermal keratinocytes. Oral studies demonstrated favorable pharmacokinetics releasing micromolar concentrations of IA or 4-MI from P2 and P13, respectively. These findings highlight the potential of prodrug strategies to enhance itaconate's cellular permeability and oral bioavailability, paving the way for clinical translation.
Keywords: Administration, Oral; myši; Prodrugs; mužské pohlaví; Rats; Drug Discovery; aplikace orální; zvířata; Humans; Mice; objevování léků; Succinates; prekurzory léčiv; sukcináty; krysa rodu Rattus; lidé; Male; Animals